Rancang Bangun Aplikasi Pengukuran Tingkat Kebugaran Berbasis Android - Efdi Aditya Pratama; Muhammad Jumnahdi; M Yonggi Puriza (EPSILON: Journal of Electrical Engineering and Information Technology, 2023)
This research is a research and development application of VO2Max measurement. VO2Max is the maximum volume of O2 that is processed by the human body during intensive activities. VO2Max is a level of the body's ability expressed in liters per minute or milliliters/minute/kg body weight. The level of a person's VO2Max is related to a person's ability to move. The higher a person's VO2Max level, the higher the activity level and the lower the fatigue level. Testing this application using a sample of 50 SKO Bangka Belitung Athletes. The Test method in this application consists of 3 measurement methods, namely: Cooper Test, Balke Test, and Beep Test. This research produces an android-based VO2Max measurement application and a practical guide to find out how to measure VO2Max or endurance. The results of the effectiveness test show that the Android-based VO2Max measurement application has no difference between manual and digital results. The function of the VO2Max measurement application is to guide the test, which makes it easier for users to carry out tests with automatic recording of results. This application uses indicators for each method, Cooper Test and Balke Test uses Distance and Time Indicators to determine the distance and time when running, the Beep Test method uses sound indicators and running animations that make it easier for users, this animation will also get faster with increasing levels. The output of the application user results to monitor and find out the VO2Max value